Comparison of different predictive tests for difficult airways in pediatrics - Kılıç, Yeliz; Onay, Meryem; Çetinkaya, Dilek; Bilir, Ayten; Büyükkıdan Yelken, Birgül (ENT Updates, 2020)
Objective: There are few studies regarding the use of predictive tests for difficult airways in pediatrics. The aim of this study was to investigate the effectiveness of the modified Mallampati test (MMT), the upper lip bite test (ULBT) and anthropometric measurements of the head and neck in the prediction of difficult airways in children. Methods: Forty-eight pediatric patients who underwent elective surgery under general anesthesia with endotracheal intubation were recruited for the study. During the preanesthetic evaluation, airway status was evaluated using three methods: MMT, ULBT and anthropometric measurements of the head and neck. Laryngoscopy was performed with a single blade of a videolaryngoscope and airway status was evaluated using the Cormack-Lehane classification. All patients were then classified into two groups: difficult airway or easy airway. Results: Ten (20.8%) patients were classified as the difficult airway group. In this group, 80% of the patients had MMT grade 3-4 (p=0.001) while 50% of the patients were classified as ULBT 3 (p=0.000). Interincisor distance (ID), hyomental distance (HMD), distance from ear tragus to the corner of the mouth (DTM) and distance from frontal plane to chin (DFC) were significantly different between the groups (p<0.05). In ROC curve analysis, ULBT had the largest area under the curve (AUC=0.880). Conclusion: ULBT, MMT, HMD and ID were the most consistent predictors of difficult airway status. ULBT was superior to other tests because of its larger AUC and higher sensitivity and specificity rates. However, difficulty in applicability in young children seemed to be the most important limitation of both ULBT and MMT.